2018
DOI: 10.3390/ijms19071983
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Suppresses Ovarian Cancer Growth via Induction of Apoptosis and Blockade of Cell Cycle Progression Involving Inhibition of the STAT3 Pathway

Abstract: A growing body of evidence has demonstrated the promising anti-tumor effects of resveratrol in ovarian cancer cells, including its inhibitory effects on STAT3 activation. Nonetheless, the low bioavailability of resveratrol has reduced its attractiveness as a potential anti-cancer treatment. In contrast, pterostilbene, a stilbenoid and resveratrol analog, has demonstrated superior bioavailability, while possessing significant antitumor activity in multiple solid tumors. In this study, the therapeutic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Releasing cytochrome c subsequently interacted with pro-Caspase-9 to activate Caspase-9 and triggered the activation of Caspase-3, contributing to apoptosis. 24) Our results showed that PTE increased the expression levels of Bax, Bak, and Bad, decreased the expression level of Bcl2, activated Caspase-9, Caspase-3 and PARP in RCC cells. Overall, these results demonstrated that induction of the Caspase-dependent mitochondria-derived apoptosis resulted in the anticancer effects of PTE in RCC cells.…”
Section: Discussionsupporting
confidence: 51%
“…Releasing cytochrome c subsequently interacted with pro-Caspase-9 to activate Caspase-9 and triggered the activation of Caspase-3, contributing to apoptosis. 24) Our results showed that PTE increased the expression levels of Bax, Bak, and Bad, decreased the expression level of Bcl2, activated Caspase-9, Caspase-3 and PARP in RCC cells. Overall, these results demonstrated that induction of the Caspase-dependent mitochondria-derived apoptosis resulted in the anticancer effects of PTE in RCC cells.…”
Section: Discussionsupporting
confidence: 51%
“…Another study has shown that siRNA mediated STAT3 downregulation suppressed SKOV3 cell growth and arrested the cell cycle in the G1 phase [70]. Several studies have highlighted that plant-derived phytochemicals, such as Pterostilbene, Cryptotanshinone and Curcumin, suppressed STAT3 activation, thereby reduced cancer cell proliferation and have been proposed as possible adjuvants of conventional chemotherapy [71][72][73].…”
Section: Proliferationmentioning
confidence: 99%
“…However, resveratrol is unstable in the environment. As a result, many derivatives of resveratrol have been studied, including PH [ 32 , 33 , 34 ]. In this study, we focused on the anti-melanogenic effects of PH and performed a mechanistic study to elucidate the signaling pathways in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, resveratrol is unstable in the environment; it is very sensitive to UVR, air, and strong pH and is easily deformed. Thus, many resveratrol derivatives have been studied, and studies have found that methylated resveratrol derivatives have a good bioavailability and bioactivity [ 32 , 33 , 34 ]. One of the methylated resveratrol derivatives, pinostilbene hydrate (3,4′-dihydroxy-5-methoxystilbene), has been demonstrated to exert strong neuroprotective activity, as well as have anti-cancer effects on human colon cancer cells and anti-metastatic effects on human oral squamous cell carcinoma (OSCC) cells [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%